2007
DOI: 10.1111/j.1399-0039.2007.00866.x
|View full text |Cite
|
Sign up to set email alerts
|

Butyrophilin‐like 2 gene is associated with ulcerative colitis in the Japanese under strong linkage disequilibrium with HLA‐DRB1*1502

Abstract: The human leukocyte antigen (HLA) region has been implicated in the pathogenesis of inflammatory bowel disease (IBD), which is classified into Crohn's disease (CD) and ulcerative colitis (UC). Recently, an association between sarcoidosis and the butyrophilin-like 2 (BTNL2) gene was reported. BTNL2 is located in the HLA region and its messenger RNA is expressed most abundantly in the intestine. In this study, we performed a case-control association study of BTNL2 in the Japanese patients with IBD and performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 49 publications
5
38
0
Order By: Relevance
“…Although such IL-6 is commonly attributed to intestinal DCs (45,46), its production by enterocytes may reinforce IL-17 production by infiltrating systemic T cells. Hence, attenuation of IL-6 expression may limit immunopathologies involving IL17-dependent neutrophilic infiltrates, consistent with the genetic associations of Btnl genes with colitis and sarcoidosis (16,18).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Although such IL-6 is commonly attributed to intestinal DCs (45,46), its production by enterocytes may reinforce IL-17 production by infiltrating systemic T cells. Hence, attenuation of IL-6 expression may limit immunopathologies involving IL17-dependent neutrophilic infiltrates, consistent with the genetic associations of Btnl genes with colitis and sarcoidosis (16,18).…”
Section: Discussionmentioning
confidence: 86%
“…Among the criteria are: they are conserved in mice and humans; several are encoded within the MHC-locus; they share strong homologies with the B7-family of costimulators; and certain murine and human Btnl/Btn gene products reportedly reduce the proliferative responses of costimulated T cells, with human BTN2A1 reportedly modulating DCs by engaging the lectin DC-SIGN (9)(10)(11)(12)(13)(14)(15). The potential importance of such interactions is further implied by genetic associations of human Btnl2 and Btn2A1 polymorphisms with sarcoidosis, myositis, and inflammatory bowel disease (16)(17)(18). Indeed, it has been proposed that Btnl proteins might be particularly important in mediating immune regulation in tissues, notably the gut (12), although the specific regulation of IEL-epithelial cell interactions by any Btnl/Btn gene has not hitherto been experimentally investigated.…”
mentioning
confidence: 99%
“…8,11 However, subsequent studies have showed inconsistent results on a sarcoidosis risk factor of BTNL2 rs2076530_A and its independent effect of HLA-DRB1. 12,13 In other diseases, such as type 1 diabetes (T1D), 14 rheumatoid arthritis (RA), 15 systemic lupus erythematosus (SLE), 14 multiple sclerosis (MS), 15 Graves'disease (GD), 16 chronic beryllium disease (CBD), 17 and ulcerative colitis (UC), 18 a significant association with BTNL2 polymorphisms appeared to be secondary to the primary HLA-DRB1 association because of its strong linkage disequilibrium (LD) with DRB1 alleles.…”
Section: Resultsmentioning
confidence: 99%
“…50 In contrast to a previous Japanese study, stratification of the BTLN2 genotypes by DRB1*1502 status demonstrated residual association at BTLN2. 51 Following on from this work, the German UC GWAS demonstrated genome-wide levels of significance at three SNPs in this region: rs9268877 (P ¼ 5.23 Â 10…”
Section: Human Leukocyte Antigen (Hla) Regionmentioning
confidence: 96%